2009
DOI: 10.1371/journal.pone.0005911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prognostic Gene Profiles Using qRT-PCR in Paraffin Samples: A Retrospective Study in Patients with Early Breast Cancer

Abstract: IntroductionGene profiling may improve prognostic accuracy in patients with early breast cancer, but this technology is not widely available. We used commercial assays for qRT-PCR to assess the performance of the gene profiles included in the 70-Gene Signature, the Recurrence Score and the Two-Gene Ratio.Methods153 patients with early breast cancer and a minimum follow-up of 5 years were included. All tumours were positive for hormonal receptors and 38% had positive lymph nodes; 64% of patients received adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Our group and others have demonstrated the clinical utility of these TLDA assays in childhood and adult clinical trials (34,35). Although current techniques such as IHC, FISH, and cytogenetics could be used to identify only a portion of medulloblastomas subgroups (21,23), our proposed 31-gene signature provides a rapid and highly accurate assay for determining these subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group and others have demonstrated the clinical utility of these TLDA assays in childhood and adult clinical trials (34,35). Although current techniques such as IHC, FISH, and cytogenetics could be used to identify only a portion of medulloblastomas subgroups (21,23), our proposed 31-gene signature provides a rapid and highly accurate assay for determining these subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the subgroups in a larger cohort of medulloblastoma patients and to validate expression of inflammation-related genes, we developed a robust and clinically applicable assay using the TLDA technology, a system currently being evaluated in neuroblastoma and used in breast cancer clinical trials (34,35). We built a medulloblastoma-specific TLDA card containing 39 tumor-related and six inflammation-related genes (CD163, CSF1R, MMD, CD4, ALCAM, and CXCR4) that were observed as significantly deregulated among medulloblastoma subgroups in our HuEx microarray analysis (Supplementary Table S2).…”
Section: Expression Of Inflammation-and Tumor Cell-related Genes Compmentioning
confidence: 99%
“…Until recently, RT‐qPCR was used only to analyse fresh‐frozen tissue samples, which yield high quality and quantity RNA. However, the recent use of this technique to analyse formalin‐fixed paraffin‐embedded (FFPE) samples has greatly facilitated retrospective studies in which correlations with surveillance and outcome are possible [5–9]. In addition, novel combined methodologies, such as the cDNA preamplification technique before gene expression analysis, allow the analysis of clinical samples that yield scarce amounts of RNA [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies showed a significant association between Oncotype DX ® and breast cancer outcome: in ER+ pN0 patients without systemic treatment,46 in ER+ pN0 patients treated with ET alone,31,36,40,42,4447 and in patients treated with chemotherapy and ET 34,41,43,46,48. An association between the RS and patients’ outcome was also found in ER+ pN+ patients 35,36,41,43,44,49,50. Only three retrospective studies evaluated the Oncotype DX ® in the target population of strictly ER+, HER2- patients 5153.…”
Section: Resultsmentioning
confidence: 99%